2015
DOI: 10.3851/imp2768
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Overall and Cause-Specific Mortality among HIV-Infected Adults on Antiretroviral Therapy in Europe, Canada and the US

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms 1 Sex differences in overall and cause-specific mortality among HIV-infected adults on Methods:The ART Cohort Collaboration (ART-CC) combines 19 cohorts of individuals started on cART in Europe and North America (NA). We analyzed patients infected via injecting drug use (IDU) or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Finally, regarding the association of gender and mortality for PLHIV, it should be taken into account that women have an overall higher life expectancy compared to men, at least in Western countries. Moreover, in PLHIV, a lower incidence of non-AIDS events in women compared to males has been described [ 22 ]. In our study, after controlling for other variables including pregnancy status and HIV viremia levels, females resulted more at risk of delayed ART initiation and therapy discontinuation, even if no differences in response rates to the first year of ART were evidenced.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, regarding the association of gender and mortality for PLHIV, it should be taken into account that women have an overall higher life expectancy compared to men, at least in Western countries. Moreover, in PLHIV, a lower incidence of non-AIDS events in women compared to males has been described [ 22 ]. In our study, after controlling for other variables including pregnancy status and HIV viremia levels, females resulted more at risk of delayed ART initiation and therapy discontinuation, even if no differences in response rates to the first year of ART were evidenced.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a lower proportion of HIV acquisition through injecting drugs in women may explain potential differences in mortality between transmission categories 26 , 27 . However, no sex differences in all-cause mortality were observed in the United States or Canada 20 . Moreover, differences in mortality by transmission category may also be modified by sex differences.…”
Section: Introductionmentioning
confidence: 89%
“…Notably, differences in mortality between different transmission categories may be confounded or modified by sex. Studies conducted in Europe 20 , China 15 , 21 , Kenya 22 , and South Africa 23 have reported that female PLWH have a lower risk of mortality than male PLWH. This is possibly because of women’s better adherence to ART 15 , 21 , lower rate of substance use 24 , or more favorable immune response to combined ART (cART) 25 .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In Canada, WLWH have poorer health outcomes across the HIV care cascade compared with men, including lower rates of access to care and adherence to cART, 14 15 more comorbidities [16][17][18] and higher mortality rates. 19 20 WLWH also experience significant psychological stressors, including gender-based violence, substance use, discrimination, the impacts of colonisation and isolation. [21][22][23] These may further accelerate biological ageing and its health impacts.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%